Two Sides of a Coin: Do Genders Affect Human-Orangutan Interactions in Lamandau Wildlife Reserve, Central Kalimantan? - Aprillyasari, Wulan Mayang; Sunkar, Arzyana; Rahman, Dede Aulia (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
Commonly, studies of human-primate interactions dwelled into general human impacts on primates. However, human gender differences might be a deeper factor to study regarding human’s perception and acceptance on primates. We investigated the influences of human gender differences on human and orangutan bi-directional receptions and analyzed the formed interactions between the two, located in Lamandau Wildlife Reserve, Central Kalimantan. We conducted interviews with 30 locals by using snowball and convenience sampling techniques, with some criteria applied. This study unveiled that orangutans displayed more promoting behaviors than inhibiting ones, suggesting that they displayed some tolerance on human’s presence around them. On the flipside, local villagers perceived orangutans differently between men and women, specifically when confronted by orangutans. We found some significant relations between human genders and orangutan behaviours, suggesting that orangutans migt view humans differently from their genders. These relations should result in correspondingly different forms of human-orangutan interactions. This study proposed a good input for designing suitable socioeconomic approaches for better orangutan conservation programs involving locals in Lamandau Wildlife Reserve.